Adaptive thermal control of stem gravitropism through alternative RNA splicing in Arabidopsis - Ryu, Jae Yong (Plant Signal Behav, 2015)
Gravitropism is an important growth movement in response to gravity in virtually all higher plants: the roots showing positive gravitropism and the shoots showing negative gravitropism. The gravitropic orientation of plant organs is also influenced by environmental factors, such as light and temperature. It is known that a zinc finger (ZF)-containing transcription factor SHOOT GRAVITROPISM 5/INDETERMINATE DOMAIN 15 (SGR5/IDD15) mediates the early events of gravitropic responses occurring in inflorescence stems. We have recently found that SGR5 gene undergoes alternative splicing to produce 2 protein variants, the full-size SGR5α transcription factor and the truncated SGR5β form lacking functional ZF motifs. The SGR5β form inhibits SGR5α function possibly by forming nonfunctional heterodimers that are excluded from DNA binding. Notably, SGR5 alternative splicing is accelerated at high temperatures, resulting in a high-level accumulation of SGR5β proteins. Accordingly, transgenic plants overexpressing SGR5β exhibit a reduction in the negative gravitropism of inflorescence stems, as observed in the SGR5-defective mutant. It is proposed that the thermos-responsive alternative splicing of SGR5 gene provides an adaptation strategy by which plants protect the shoots from aerial heat frequently occurring in natural habitats.